Shadow theatre and scenic lighting (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
Based on the concepts of Reiner Reush, Fabrizio Montecchi and David Currel, the paper addresses the three styles of shadow theatre - the Traditional, the Modern and the Contemporary – and discusses technical and aesthetic aspects of scenic lighting based on experiences of theatrical creation developed in a Laboratory of Puppet Theatre in Rio de Janeiro, Brazil. The paper’s purpose is to show the coexistence of styles as a fundamental feature of contemporary culture. The context of the Covid-19 pandemic led to the resumption of some styles that have apparently been overcome.
Keywords: shadow theatre; scenic lighting; creation process